Discretionary Accounting Accruals, Managers' Incentives, and Audit Fees* - Gul, Ferdinand A.; Chen, Charles J. P.; Tsui, Judy S. L. (Contemporary Accounting Research, 2003)
Abstract This paper examines the linkages between discretionary accruals (DAs), managerial share ownership, management compensation, and audit fees. It draws on the theory that managers of firms with high management ownership are likely to use DAs to communicate value‐relevant information, while managers of firms with high accounting‐based compensation are likely to use DAs opportunistically to manage earnings to improve their compensation. OLS regression results of 648 Australian firms show that (1) there is a positive association between DAs and audit fees; (2) managerial ownership negatively affects the positive relationship between DAs and audit fees; and (3) this negative impact is further found to be weaker for firms with high accounting‐based management compensation.